Breast fibrocystic change and Page's classification - Ahmad Ghozali Ahmad Ghozali (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1994)
Fibrocystic change is a benign breast lesion commonly found in women. In the past this lesion was regarded as having a high potential malignancy. By using Page's classification, Dupont and Page histologically proof that most of fibrocystic lesions (69,7%) have equal risk for malignancy with normal women population. Only 4% of the benign breast lesion have high risk to become breast carcinoma.The study of Dupont and Page has changed the terminology and point of view regarding malignant potency of the fibrocystic lesion of the breast. In the future pathologists are recommended to apply Page's classification in order to treat the patient with fibrocystic lesion more properly.Key words: fibrocystic change-carcinoma in situ of the breast-Page's classification-a typical hyperplasia-breast cancer